KEABSAHAN TANDA TANGAN ELEKTRONIK (ELECTRONIC SIGNATURE) DALAM PERDAGANGAN DITINJAU BERDASARKAN KITAB UNDANG-UNDANG HUKUM PERDATA - Christi Ningrum Blegur Laumuri, Maria Margaretha; Ari Yuliartini Griadhi, Ni Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014, 2014)
This paper titled Legality of Electronic Signature in the commerce are reviewed by the Burgerlijk Wetboek, which is also the subject matter to be discussed in this paper. Based on of this paper is using of electronic signature in business transaction that is currently prevalent in the electronic certificate or sell and purchase contract electronic form after the development of information, technology especially internet. The purpose of this paper is recognize concerning force of law or legality and legal consequences of electronic signature reviewed by the Burgerlijk Wetboek. This paper uses the normative method by analyzing the cases with the Act and in other related literature. The conclusion in this paper is the force of electronic signature in the commerce are reviewed by the Burgerlijk Wetboek is legal and similar with manual signature, that is attached to an general agreement or contract commerce. Legal consequencesof electronic signature has legal binding and valid as a act for both parties as provided in Article 1338 of the Burgerlijk Wetboek.
Keywords: Legality, Electronic Signature, Burgerlijk Wetboek, and E-commerce